Perfectionist self-presentation during chilhood and its association with school anxiety - María del Pilar Aparicio- Flores; María José Hernández- Amorós; María Encarnación Urrea- Solano; Aitana Fernández- Sogorb (INFAD, 2018)
Perfectionist Self-Presentation (PSP), known as the desire to project a perfect image towards others with protective characteristics of its social exhibition and with the reiterative need to divulge excellent, is one of the most influential in psychopathology derived factors, and one of the less studied in the educational context. The aim of this study was to examine the relationship between PSP and School Anxiety in a sample of 860 participants aged between 8 and 12 years (M = 9.86; SD = 1.26), registered in public and private centers of the province of Alicante. We used the Perfectionistic Self-Presentation Scale Junior Form (PSPS-Jr) and the Inventario de Ansiedad escolar para Educación Primaria (IAEP). Statistical analyzes revealed a positive and significant association between PSP and School Anxiety in all of its factors and the total of its scales, with a high correlation between Non-Disclosure of Imperfection and Anxiety in School Punishment. Taking to these considerations, this study evidences specific characteristics that determine the design of a possible treatment to decrease maladaptive personality traits in the child and youth population.